Bio-efficacy of Nanosilicon in Regulating Oxidative Activity to Control Rice Seedlings Rot Disease Caused by Burkholderia glumae - Tamilselvan R. Govinda Rajoo; Muhamad Syazlie Che Ibrahim; Aziz Ahmad; Lee Chuen Ng (The Plant Pathology Journal)
Bacterial panicle blight and seedling rot diseases in rice plants (Oryza sativa L.) are caused by the pathogenic bacterial Burkholderia glumae. The nanosilicon treatment is gaining attraction but its effectiveness towards B. glumae infection in rice seedlings through regulating enzymatic activities remains largely unexplored. This study aimed to evaluate the bio-efficacy of nanosilicon in controlling seedling rot disease through regulation of peroxidase and polyphenol oxidase enzymes after challenge infected with B. glumae in rice variety MR297 and PadiU Putra. Nanosilicon was applied as seed priming in germination testing at 0, 300, 600, and 900 ppm on both rice varieties before B. glumae inoculation. Both rice seed varieties primed with nanosilicon at 600 ppm exhibited a significant increase in seedling germination performances over control. The rice seedling of MR297 was more responsive to nanosilicon at 600 ppm with only 17.78% of disease severity index over 26.67% in PadiU Putra and was therefore selected for the enzymatic activity screening. The results showed that the foliar spray of nanosilicon rice plants (MR297) significantly increased both peroxidase (POX) at 24 h and polyphenol oxidase (PPO) at 48 h after B. glumae inoculation with 20.44/min/g and 7.46/g activities, respectively. In addition, the plant growth performances were significantly increased compared with control under the same treatment. This demonstrates nanosilicon’s potential to control rice seedling rot disease by regulating POX and PPO activities and hence promote plant growth. The application of nanosilicon is an environmentally friendly approach for controlling B. glumae infection at the early rice growing stage.